2018
DOI: 10.3390/s18030922
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Tracking System for Running Race Applications Based on Bluetooth Low Energy Technology

Abstract: Timing points used in running races and other competition events are generally based on radio-frequency identification (RFID) technology. Athletes’ times are calculated via passive RFID tags and reader kits. Specifically, the reader infrastructure needed is complex and requires the deployment of a mat or ramps which hide the receiver antennae under them. Moreover, with the employed tags, it is not possible to transmit additional and dynamic information such as pulse or oximetry monitoring, alarms, etc. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…(which was not certified by peer review) based on waiting time surveys was used. As described below, unique barcodes and hand-held barcode scanners were used instead of radio-frequency identification tags [36][37][38] or a paper-based system. [30]…”
Section: Methodsmentioning
confidence: 99%
“…(which was not certified by peer review) based on waiting time surveys was used. As described below, unique barcodes and hand-held barcode scanners were used instead of radio-frequency identification tags [36][37][38] or a paper-based system. [30]…”
Section: Methodsmentioning
confidence: 99%
“…Among available solutions, Bluetooth Low Energy (BLE) is gaining more and more popularity [3]. Small, embedded sensors that communicate via BLE are used in everyday life for a wide number of applications such as wearable devices, smart homes, home automation, e-health systems, indoor positioning, traffic control, and telemedicine [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,21].…”
Section: Introductionmentioning
confidence: 99%
“…A study in which each runner wore a Bluetooth Low-Energy (BLE) device and received the BLE device's broadcast signal from a mobile phone showed that this system could achieve a 100% acquisition rate of the timing score and actively transmitted information that individual runners required [6]. However, the trick is to track the time points that the runners pass through every radius of a fixed point on the track within 25 m or 12.5 m. In addition, because this is through a large range of receiving blocks, the time difference that is received will be obviously enlarged.…”
Section: Introductionmentioning
confidence: 99%